The agriculture, food and health challenge: critical issues, perspectives and options - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
This ‘Critical Issues, Perspectives and Options’ (CIPO) publication provides some broader long-term development perspectives on the subject. This issue builds on a previous and first such publication which addressed critical issues related to the first Key Binding Constraint – Limited Financing and Inadequate Levels of New Investments in Agriculture. The perspectives on ‘The Agriculture, Food and Health Challenge’ is offered in contribution to the regional dialogue and decision-making on the widening challenges and roles of agriculture in meeting the food and nutrition needs of CARICOM